Contract cheating: a survey of Australian university students. Issue 11 (2nd November 2019) - Bretag, Tracey; Harper, Rowena; Burton, Michael; Ellis, Cath; Newton, Philip; Rozenberg, Pearl; Saddiqui, Sonia; van Haeringen, Karen
ABSTRACT: Recent Australian media scandals suggest that university students are increasingly outsourcing their assessments to third parties – a behaviour known as 'contract cheating'. This paper reports on findings from a large survey of students from eight Australian universities ( n = 14, 086) which sought to explore students' experiences with and attitudes towards contract cheating, and the contextual factors that may influence this behaviour. A spectrum of seven outsourcing behaviours were investigated, and three significant variables were found to be associated with contract cheating: dissatisfaction with the teaching and learning environment, a perception that there are 'lots of opportunities to cheat', and speaking a Language Other than English (LOTE) at home. To minimise contract cheating, our evidence suggests that universities need to support the development of teaching and learning environments which nurture strong student–teacher relationships, reduce opportunities to cheat through curriculum and assessment design, and address the well-recognised language and learning needs of LOTE students.